Estrogen metabolites and their relation to isoprostanes as a measure of oxidative stress - Sowers, MaryFran (2007)
OBJECTIVE: Estradiol (E2) and its metabolites [2-hydroxyestrone (2-OHE1) and 16α-hydroxyestrone (16α-OHE1)] are believed to curtail greater oxidative stress found in the development and progression of disease conditions including atherosclerosis. We related estrogen levels to F2(a)-isoprostane levels, a biomarker of oxidative stress. DESIGN AND PARTICIPANTS: Data were from 1647 women, aged 47-57 years, participating in the 5(th) annual follow-up of the Study of Women's Health Across the Nation (SWAN), a study of the menopausal transition. MEASUREMENTS: Serum E2 and urinary 2-OHE1 and 16α-OHE1 concentrations were assayed by ELISA while urinary F(2a)-isoprostanes were assayed by EIA. RESULTS: F(2a)-isoprostane concentrations were elevated in women who smoked, a behavior associated with increased oxidative stress, but not in stages of the natural menopause. Mean F(2a)-isoprostane concentrations among premenopausal and postmenopausal women who smoked were 1082 and 1064 pg/mL, respectively, values double those in premenopausal (343 pg/mL) and postmenopausal (379 pg/mL) non-smoking women. 2-OHE1 and F(2a)-isoprostane concentrations were positively and highly related [partial correlations ρ(Y|X) = 0.44 and ρ(Y|X) = 0.43 in premenopausal and postmenopausal women, respectively]. Likewise, 16α-OHE1 concentrations were positively and highly correlated with F(2a)-isoprostane concentrations [ρ(Y|X) = 0.52 and ρ(Y|X) = 0.59 in premenopausal and postmenopausal women, respectively]. E2 was significantly correlated with F(2a)-isoprostanes only in postmenopausal women [ρ(Y|X) = 0.20]. Associations were adjusted for age, body mass index, race/ethnicity, lipids, physical activity level, and alcohol consumption. CONCLUSIONS: This study does not support the commonly-held hypothesis that levels of endogenous estradiol or its estrone metabolites favorably modify oxidative stress by decreasing F2(a)-isoprostane levels.